Technique for Measuring Spatial Distribution of the Surface Acoustic Wave Velocity in Metals - MOKRYY, Oleh; TSYRULNYK, Oleksandr (Archives of Acoustics, 2016)
In this paper a possibility of determining a local velocity of the surface acoustic Rayleigh waves using a transducer, with the rigidly connected emitting and receiving parts, is considered. A problem on spatial resolution of such a transducer for investigation of inhomogeneous specimens is also examined. A high spatial resolution can be obtained due to the transducer displacement by a value less than the distance between the emitting and receiving parts. It is shown that in this case it is not necessary to measure the transducer displacement with a high accuracy for precise determination of the velocity. Such an effect is obtained through measuring the velocity of surface waves in one local region of the specimen with respect to the other. The criterion for optimal spatial resolution selection during spatially inhomogeneous specimens study is also proposed. The proposed criterion use is illustrated on the example of the determination of spatial distribution of the surface acoustic velocity in a steel specimen subjected to inhomogeneous plastic deformation.